Response of Human Macrophages to Clinically Applied Wound Dressings Loaded With Silver - Varela, Patrícia; Marlinghaus, Lennart; Sartori, Susanna; Viebahn, Richard; Salber, Jochen; Ciardelli, Gianluca (Frontiers in Bioengineering and Biotechnology, 2020)
Wound infections constitute an increasing clinical problem worldwide. To reverse this trend, several wound dressings with antimicrobial properties have been developed. Considering the increasing presence of antibiotic-resistant microorganisms, product developers have been focusing their efforts in introducing antibiotic-free antibacterial wound dressings to the market, with silver being the most commonly incorporated antimicrobial agent. In this scenario, gaining information about the microbial and eukaryotic cells’ response to these dressings is needed for a proper selection of antimicrobial dressings for the different cases of infected wounds. In particular, one insufficiently explored parameter is the effect of the dressings on the immunomodulation of macrophages, the main immune cell population participating in the repair process, because of their pivotal role in the transition of the inflammation to the proliferation phase of wound healing. In this work, three different clinically applied antimicrobial, silver impregnated wound dressings were selected: Atrauman® Ag, Biatain® Alginate Ag and PolyMem WIC Silver® Non-adhesive. Antimicrobial susceptibility tests (disk diffusion and broth dilution), cell viability evaluation (CellTiter-Blue®) and experiments to determine macrophage polarization (e.g. flow cytometry, ELISA and glucose uptake) were performed after 24 hours of incubation. Among all products tested, Biatain® Alginate Ag induced the most evident bactericidal effect on Gram-positive and Gram-negative bacteria, followed by PolyMem WIC Silver® Non-adhesive, but did not show good cytocompatibility in vitro. On the other hand, Atrauman® Ag showed excellent cytocompatibility on L929 fibroblasts, HaCaT keratinocytes and THP-1 derived macrophages, but no significant antimicrobial activity was observed. Overall, it was confirmed that macrophages initiate, in fact, an alteration of their metabolism and phenotype in response to wound dressings of different composition in a short period of contact (24 hours). M0 resting state macrophages common response to all silver-containing dressings used in this study was to increase the production of the anti-inflammatory cytokine TGF-β, which indicates an acquisition of M2-like macrophages characteristics.